ANALISIS IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DALAM KURIKULUM MERDEKA SISWA KELAS V SD N SIDOMULYO REMBANG - Dhimas Prasetyo; Gunawan Setiadi; Ika Ari Pratiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of the Project to Strengthen the Profile of Pancasila Students (P5) at SD N Sidomulyo, including the challenges encountered and the solutions provided. Conducted in Grade V with 22 students (11 boys and 11 girls), the project involved growing mustard greens as a practical activity. Data were collected through observations, interviews, and documentation, analyzed using Miles and Huberman's qualitative approach involving data reduction, presentation, and verification. The findings show that the project was well-executed, following steps such as identifying initial needs, project planning, scheduling, supervision, evaluation, and assessment. However, several challenges arose, including poor teamwork among students, limited coordination with parents, and pest issues. The school addressed these problems through intensive supervision, regular communication with parents via WhatsApp, and the use of pesticides to manage plant pests.